Berberine from roots of Berberis aristata prevents cataract formation in isolated goat eye lens An In-vitro Study - Dave, Kapilesh (International Journal of Pharmaceutical & Biological Archive, 2013)
Berberine from roots of Berberis aristata prevents cataract formation in isolated goat eye lens An In-vitro Study